Vulgar and spam comment identification using Gluon Natural Language Processing and Convolution Neural Networks - Jahan, Rufyda (BRAC University, 2019)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2019.